1717c Biological monitoring and the use of guidance values in assessing occupational exposures. (24th April 2018) - Jones, Kate
Abstract : Biological monitoring is a useful tool for assessing systemic exposure, particularly for substances absorbed through the skin or where control of exposure relies on respiratory protection. Many organisations propose health-based guidance values (BMGVs) but recognise that there are no 'bright lines' between safe and unsafe levels and avoid the word 'limits'. Where a health-based BMGV is not possible, a non-occupational exposed background or reference value may be proposed. Exceeding such a reference value then indicates the likelihood of occupational exposure and possibly the need to review workplace controls. Great Britain (GB) has an alternative approach based on the 90th percentile value of biological monitoring data from workplaces following good occupational hygiene practice. It is not health-based and exceeding it simply indicates a need to review, and possibly improve controls. This presentation will give an overview of biological monitoring, its role in occupational exposure assessment and the derivation and use of guidance values in interpreting results and determining future action.